Peningkatan Hasil Belajar dan Kemandirian Belajar Metode Statistika Melalui Pembelajaran Blended Learning - Ningsih, Yunika Lestaria; Misdalina, Misdalina; Marhamah, Marhamah (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
This study aims to: (1) Know the differences in student learning outcomes between the Blended Learning model and ordinary learning both overall and based on the level of early math ability (high, medium and low), (2) Knowing the increase in student self-reliance taught by using Blended Learning models and students are taught with ordinary learning both overall and by the level of early math ability (high, medium and low). in this research use method that is quasi-experiment with pretest-postest control group design design. The population in this research consists of all 5th-semester students of Mathematics Education Study Program Universitas PGRI Palembang Academic Year 2016/2017. The sample in this research is class 5B (control class) and 5C (experiment class). Data collection with self-study test and questionnaire. Data analysis was performed using t-test statistic and t'-test. The result of the research shows that (1) the improvement of students' learning outcomes taught by using Blended Learning model is higher than students who are taught with ordinary learning both overall and based on the level of early math ability (high, medium and low), (2) improvement of learning independence students who were taught using the Blended Learning model were higher than students who were taught with ordinary learning in terms of overall, high and moderate levels of math skills, but not higher at lower levels.